Classroom Praxis of Applied Oral Communication Strategies in Enhancing English Speaking Skills in Indonesian Secondary School - KAFABIH, Abdullah; HERDA, Rozanah Katrina; MONTEZA, Ana Mae M (Research and Innovation in Applied Linguistics, 2025)
Speaking is widely recognized as one of the most challenging skills for EFL students to acquire, due to its demand for real-time language processing, confidence, and adequate linguistic resources. This mixed-method study investigates students’ perceived difficulties in speaking English, combining questionnaire data from 91 participants and semi-structured teacher interviews as the instruments. Quantitative findings reveal that learners experienced significant affective barriers, including low self-confidence, fear of making mistakes, and nervousness when speaking in front of others. Linguistic limitations, particularly restricted vocabulary and pronunciation challenges, were also found to disrupt fluency and promote reliance on first-language translation. Furthermore, insufficient opportunities to practice speaking and limited support outside the classroom emerged as additional constraints. The qualitative data reinforced these issues, pointing to motivational gaps and institutional limitations. The findings provide valuable insights into the multifaceted nature of speaking difficulties and suggest actionable pedagogical responses. Drawing on theories of Foreign Language Classroom Anxiety and sociocultural learning, the study emphasizes the need for learner-centered instruction that fosters emotional security, meaningful interaction, and increased speaking opportunities. These include the integration of digital tools to reduce anxiety, implementation of peer interaction activities, pronunciation-focused tasks, increased speaking time in lessons, and more structured teacher feedback practices. The study also points to the potential of longitudinal research to track the development of speaking proficiency over time. Keywords: EFL learners, speaking anxiety, linguistic challenges, classroom interaction, language learning